"I just want to keep in touch": Adolescents' experiences with leisure-related smartphone use. (26th May 2020) - Allaby, Michaela; Shannon, Charlene S.
Abstract: The widespread adoption and integration of smartphones into daily life has meant that adolescence is a period of development influenced by smartphones. Given that leisure is an important developmental context for adolescents, the purpose of this study was to explore adolescents' experiences with having and using smartphones and how those experiences influenced their leisure. Hermeneutic phenomenology guided this research. Semi-structured, face-to-face interviews were conducted with nine participants (five males and four females), between the ages of 14 and 17, to develop an understanding of the nature and meaning of their lived experiences with their smartphone. Findings highlighted that smartphones were central in the adolescents' lives. The device was used to alleviate boredom during unstructured leisure time and served both as a draw and distraction when youth were engaged in leisure activities. Smartphones were also described as offering low commitment leisure opportunities for youth to relax and interact with their friends.